An upper bound on Reidemeister moves - Coward, A; Lackenby, M (Johns Hopkins University Press, 2014)
We provide an explicit upper bound on the number of Reidemeister moves required to pass between two diagrams of the same link. This leads to a conceptually simple solution to the equivalence problem for links.